System-Forming Signs of the Legislative Power in the Russian Federation - Gulnara Nikolaevna Kopiatina (Управленческое консультирование)
The article is devoted to the reveal and observe of the system-forming signs of the legislative power in the Russian Federation. The unity of the legislative power system is being regarded through a prism of federal relations, because the author is concentrating on the interaction of the legislative power organs of the Russian Federation and its regions.